Educação cidadã através da redação do enem: autoria e argumentação - (:unkn) unknown (Universidade Federal do Pampa, 2026)
The present study sought to investigate strategies to overcome the difficulties encountered by students in the production of argumentative essays, specifically with regard to the construction of argumentation and the manifestation of authorship. The research was based on the perception that school writing involves challenges that go beyond the mastery of textual structure, also encompassing forms of positioning, the mobilization of a sociocultural repertoire, and the relationship with social issues. Therefore, the objective of this research focused on analyzing the effects of an intervention proposal on difficulties related to authorship and the development of argumentation in the production of argumentative texts by high school students, from the perspective of citizenship education. Specifically, the study sought to: diagnose the main difficulties encountered by students in the construction of argumentative texts; develop preparatory activities for the ENEM essay from the perspective of argumentation and authorship; offer an extension course to high school students in the city of Pinheiro Machado/RS; analyze students’ performance in the activities developed; and construct a pedagogical product to support teachers in working with argumentative texts in the classroom from a citizenship-oriented perspective. The research was grounded in discussions on Argumentation, Authorship, and Critical Literacy, drawing on authors such as Fiorin (2018), Koch and Elias (2016), and Hoppe (2014). Of a qualitative and intervention-based nature, the action research was carried out through an extension course focused on ENEM writing, in which reading activities, thematic discussions, production of argumentative texts, and guiding feedback were developed. The intervention showed that writing, revising, and rewriting do not correspond to an automatic act, but rather to a gradual process, in which students experiment with ways of organizing ideas, selecting information, and expressing points of view. The analyses showed that students made progress, especially in expanding the content mobilized and in the attempt to establish greater articulation between parts of the text. Overall, the study shows that the teaching of writing requires pedagogical practices that consider textual production as a continuous process, reinforcing the importance of authorship and argumentation in school.
Weaving arguments and constructing authorship: civic education through argumentative essays
Keywords: Argumentação; Autoria; Educação cidadã; Redação do ENEM; Argumentation; Authorship; Civic education; ENEM essay; LINGUISTICA, LETRAS E ARTES